Two Ways To count To Ten - Ruby Dee (Henry Holt And Company, 1988)
"Meddaugh's color-pencil and watercolor paintings suit the text well; they leand extra dimension to the animals' characterizations as the story unfolds. Readers and listeners of all ages will find this an irresistibly satisfying tale".--Publishers Weekly.